Phenotypic recurrent selection for early flowering of ’Carioca’ common bean - Silva, Flávia Barbosa; Ramalho, Magno Antonio Patto; Abreu, Ângela de Fátima Barbosa (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the efficiency of phenotypic recurrent selection for the number of days until blooming in common bean, and to verify if this selection affected other traits. One S0 population derived from the mixture of the F2 populations of 11 hybrid combinations evaluated for earliness was used. The plants of the S0 (cycle 0) which bloomed first were crossed to obtain cycle I. To go on with the selection the obtained seeds were used. The process was repeated until the fifth selection cycle. Fifty-three S1:2 progenies of each cycle were used for evaluation of the genetic progress. The number of days to flowering, severity of angular leaf spot (Phaeoisariopsis griseola), number of days to maturation, yield and grain type were evaluated. A selection gain of 2.2% per year was observed, which indicates that phenotypic recurrent selection reduced the number of days to flowering. The selection for the number of days to flowering had no correlated response with other evaluated traits, indicating that progeny selection for early flowering can be associated with the phenotypic expression of other traits, according to the breeder’s interest.